Beef Marketing Channels and Efficiency in Banyumas Regency Central Java Indonesia - Widiyanti, Rahayu; Hidayat, Nunung Noor; Mastuti, Sri (Technium Sustainability, 2024)
The research was conducted in Banyumas Regency, with the objectives of studying 1) beef marketing channels, 2) beef marketing margins, and 3) beef marketing efficiency. To achieve this goal, a survey research method was used, with the research targets being beef cattle wholesellers, beef marketing institutions, and beef consumers. Slaughterhouses (RPH) were selected using a purposive sampling method; they were RPH Purwokerto and RPH Ajibarang. From each RPH, eight beef cattle whole sellers were selected as respondents, from which five retailers were selected. By using the accidental sampling method, two buyers were selected from each retailer. Therefore, there were 96 respondents from each RPH, or 192 in total. The data analysis used included descriptive analysis and marketing analysis, including costs, profits, and marketing margins. The results obtained were that there were two marketing channels, namely: (1) RPH/butcher à wholesalers à stall tradersà consumers; (2) RPH/butcher à wholesalers à consumers. The marketing margins were IDR 34,346 and IDR 26,845, and the marketing efficiency was 4.04% and 2.86% in marketing channel 1 and marketing channel 2, respectively. It can be concluded that the beef marketing channel is simple, with quite high marketing efficiency.